2011
DOI: 10.1093/toxsci/kfr096
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Clusterin in Prostate and DNA Damage in Spermatozoa from Bisphenol A–Treated Rats and Formation of DNA Adducts in Cultured Human Prostatic Cells

Abstract: Among endocrine disruptors, the xenoestrogen bisphenol A (BPA) deserves particular attention due to widespread human exposure. Besides hormonal effects, BPA has been suspected to be involved in breast and prostate carcinogenesis, which share similar estrogen-related mechanisms. We previously demonstrated that administration of BPA to female mice results in the formation of DNA adducts and proteome alterations in the mammary tissue. Here, we evaluated the ability of BPA, given with drinking water, to induce a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 40 publications
1
34
0
4
Order By: Relevance
“…BPA exposure was previously shown to cause DNA damage in human sperm[7] and murine sperm[43]. The transcripts of some DNA damage-associated genes are abundant in human sperm [39].…”
Section: Resultsmentioning
confidence: 99%
“…BPA exposure was previously shown to cause DNA damage in human sperm[7] and murine sperm[43]. The transcripts of some DNA damage-associated genes are abundant in human sperm [39].…”
Section: Resultsmentioning
confidence: 99%
“…In the adult rat prostate, low- and high-dose BPA exposure has been reported to adversely increase clusterin levels and expression of aromatase, while decreasing levels of 5α-reductase type 1 and 2 (Castro et al 2013; De Flora et al 2011; Sánchez et al 2013). Interestingly, Castro et al (2013) and De Flora et al (2011) reported that BPA exposure increased the plasma estradiol to testosterone ratio, which has been implicated in the development of benign prostate hyperplasia (Nicholson et al 2012; Nicholson and Ricke 2011). Further, gestational exposure to low-dose BPA increased gene expression of androgen receptor, Esr1 , aromatase, and estrogen-related receptor γ in the mouse prostate (Arase et al 2011).…”
Section: Male Urinary Tractmentioning
confidence: 99%
“…The levels of hydrogen peroxide (H 2 O 2 ) and lipid peroxidation were also increased in testes and spermatozoa of BPA-treated animals. In another study, testicular antioxidant enzymes were impaired by a very low-dose (viz., 0.005 mg/kg bwt/day) of BPA following 45 days of exposure (De Flora et al 2011 ;D'Cruz et al 2012 a, b). BPA also decreased antioxidant enzyme activities and induced lipid peroxidation in both epididymides and sperm cells (Chitra et al 2003a ) (Fig.…”
Section: Effects Of Bisphenol a On The Testicular And Epididymal Antimentioning
confidence: 99%
“…1: spermatogonium; 2: preleptotene spermatocyte; 3: pachytene spermatocyte; 4: round spermatid; 5: elongated spermatid; 6 and 7: spermatozoa, before and after capacitation, respectively. Abbreviations: BTB blood-testis barrier, E2 estradiol, LC Leydig cell, FSH follicle-stimulating hormone, GnRH gonadotropin-releasing hormone, SC Sertoli cell, T testosterone (De Flora et al 2011). Meeker et al ( 2010 also studied human male partners of subfertile couples seeking treatment from the Vincent Andrology Lab at Massachusetts General Hospital, and observed increased DNA damage in sperm, and reduced semen quality that were associated with BPA exposure (Fig.…”
Section: Effects Of Bisphenol a On Sperm Functionmentioning
confidence: 99%